Painting the Novel Pictorial Discourse in Eighteenth-Century English Fiction - Lipski, Jakub (British Literature in Context in the Long Eighteenth Century, 2018)
Painting the Novel: Pictorial Discourse in Eighteenth-Century English Fiction focuses on the interrelationship between eighteenth-century theories of the novel and the art of painting - a subject which has not yet been undertaken in a book-length study. This volume argues that throughout the century novelists from Daniel Defoe to Ann Radcliffe referred to the visual arts, recalling specific names or artworks, but also artistic styles and conventions, in an attempt to define the generic constitution of their fictions. In this, the novelists took part in the discussion of the sister arts, not only by pointing to the affinities between them but also, more importantly, by recognising their potential to inform one another; in other words, they expressed a conviction that the theory of a new genre can be successfully rendered through meta-pictorial analogies. By tracing the uses of painting in eighteenth-century novelistic discourse, this book sheds new light on the history of the so-called "rise of the novel".